Pengujian Black Box pada Aplikasi Verifikasi Data Nasabah dengan Menggunakan Metode Boundary Value Analysis - Lailan Cipta Hermawan; Moh. Rizki Mubarok; Hidayat Mairudin; Ahmad Mahdiyan; Yulianti Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Testing is one level that must be passed in order to produce results from a weighted sistem. If no testing is done on the sistem, the quality of the sistem cannot be known so that if an error occurs it can harm the sistem. By conducting experiments can find the location of defects in a sistem that can be known from the beginning that can be fixed immediately. Testing there are several types of sistem experiments, experiments used are Black Box testing using a limit value analysis method that is effective in trying the functions of a sistem. Testing techniques by making test cases based on limits on lower and upper values can provide good coverage and represent the actual input values. Based on the results of tests conducted with the analysis of boundary values, the application developed has been error free. This gives a guarantee that the application developed has met the requirements and is of high quality.